EFISIENSI PENERAPAN ABC TERHADAP SEKTOR PUBLIK - Sinaga, Averia; Gea, Riris Setiofani; Saribu, Ardin Dolok; Br. Tarigan, Zoyce Natalia; Lumbangaol, Herawati; Nainggolan, Desi Aminarti; Sinaga, Elisabet; Panjaitan, Rizky; Sirait , Yonatan (Komunitas Manajemen Kompetitif, 2024)
In the main Journal, The implementation of Activity Based Costing (ABC) in the South African public sector has significant benefits in improving financial management practices and decision making. ABC helps in allocating costs more accurately, improving operational efficiency, and supporting better strategic decision-making.Challenges in the implementation of ABC in the public sector include the insufficient number of local governments in South Africa that have implemented this method.This research makes an important contribution in expanding knowledge about the implementation of ABC in the public sector, especially in South Africa. The comprehensive review in this journal can serve as a foundation for further research and provide practical guidance for public sector organizations in improving their financial management.